Determining the distribution factors of an endangered large carnivore: A case study of the brown bear Ursus arctos population in the Central Zagros Mountains, Southwest Iran - Ashrafzadeh, Mohammad Reza; Shahbazinasab, Kamalaldin; Mohammadi, Alireza; Penterani, Vincenzo (Global Ecology and Conservation, 2023)
Human encroachment in natural habitats and consequent landscape modifications pose significant threats to animal populations, particularly endangered species. Therefore, studying the factors that determine the spatial distribution of large carnivores, including those at risk, holds great significance in developing effective conservation strategies. Among the most endangered bear populations worldwide, the conservation of the brown bear Ursus arctos population in the Central Zagros Mountains (southwestern Iran), which represents the species’ southernmost geographical range, is currently facing serious challenges. However, little is known about the species’ geographical range and the critical factors affecting its distribution in this area. Here, we employed a modelling approach to estimate the geographical distribution of this brown bear population and identify the primary landscape features that contribute to the species’ distribution. Our analysis revealed the following findings: (1) about 45% of the study area comprises suitable habitat for brown bears; (2) main factors influencing bear distribution, along with their respective contributions, are (a) distance to conservation areas and prohibited hunting areas (CAs/PHAs; 33.7%), (b) maximum temperature during the warmest month (21.6%), (c) landscape roughness (14.8%), (d) forest density (11.2%) and (e) mean annul precipitation (10.6%); and (3) roughly 69% the predicted suitable habitats exist outside CAs/PHAs. This highlights the importance of considering areas beyond CAs/PHAs in future conservation strategies, were the connectivity among forest patches is crucial for bear survival. The recent escalation of human activities, such as the harvesting of natural resources (e.g., medicinal and aromatic plants, fruits and honey), orchard and agricultural development, overgrazing of livestock, and the construction of water transfer infrastructures from the mountains to downstream regions, raises significant concerns for bear conservation in the study area. These ...